Pengaruh Pendapatan Asli Daerah Dan Dana Perimbangan Terhadap Belanja Daerah Pemerintah Kota Kendari - Misnawati (Jayapangus Press, 2019)
This study aims to determine the magnitude of the Effect of Regional Original Revenue and Balancing Funds on Regional / Regency Spending in Southeast Sulawesi Province. The population in this study amounted to 17 districts / cities in Southeast Sulawesi Province whose data is published in the Central Statistics Agency, with the sampling technique using purposive sampling techniques with certain criteria so that the sample of this study amounted to 6 districts / cities using multiple linear regression analysis as a method data analysis. The results of this study indicate that the Regional Revenue and Balancing Fund simultaneously influence the Regional Spending Allocation to the Regency / City Government in Southeast Sulawesi. While partially, the Original Local Revenues have a significant impact on the allocation of Regional Expenditures. While the Balancing Fund also has a significant effect on the allocation of district / city expenditure in Southeast Sulawesi.